Armstrong’s Theory of Laws and Causation: Putting Things into their Proper Places - Shirazi, S. M. Hassan A. (Problemos, 2018)
[full article, abstract in English; abstract in Lithuanian] Armstrong’s theory of laws and causation may be articulated as something like the following, which we may refer to as the received view: “Laws are intrinsic higher-order relations of ensuring (necessitation) between properties. The instantiation of laws is identical with singular causation. This identity is a posteriori.” Opponents and advocates of this view, believe that it may fairly and correctly be attributed to Armstrong. I do not deny it; instead I seek to reconsider the received view, specifically by treating it as a part of Armstrong’s metaphysics. The main features that should concern us are truthmaker theory and the formal account of the constitutive parts of states of affairs. I also discuss Bird’s ultimate argument against Armstrong and show how its impact is weakened by this proper reading.